DRUG RESISTANCE OF MYCOBACTERIUM TUBERCULOSIS IN DIFFERENT LOCALIZATIONS OF THE DISEASE - P. K. Yablonskii (Sankt-Peterburg : NIIÈM imeni Pastera, 2016)
The long-term Mycobacterium tuberculosis drug resistance monitoring data were obtained in St. Petersburg Research Institute Phthisiopulmonology for four periods of observation (I — 1984–1988 years, start period; II — 1996–2000 years, the period of acute epidemic situation and the sharp rise in drug resistance; III — 2007–2011 years, the period of relative stabilization; IV — 2012–2014 years, the final period). Totally 2267 strains from patients with pulmonary tuberculosis, treated previously and with chronic process, and 691 strains from patients with extrapulmonary tuberculosis were studied. Researches of drug resistance were made by indirect method of absolute concentrations in the medium Lowenstein–Jensen and in the automated system ВАСТЕС™ MGIT™ 960 (Becton Dickinson, USA). It shows a steady increase of the overall drug resistance, which has reached in the last three years 90.1% in pulmonary tuberculosis. At the same time there was a sharp worsening of the structure of drug resistance due to the growth of multidrug (MDR) and extensively drug-resistant (XDR), which by 2014 accounted for 81.9 vs 28.5% in 1984–1988. In extrapulmonary tuberculosis the growth of drug resistance of Mycobacterium tuberculosis continues to outpace: overall drug resistance increased from 39.4% (1984–1988) to 80.2% (2012–2014), reaching figures that are comparable to those of pulmonary tuberculosis. At the same time there was an even more rapid change for the worse of its structure due to the increase of MDR/XDR strains: from 10.5% in the first period to 69.5% in the fourth. This is due to the more frequency of existing in locus of extrapulmonary tuberculosis of highly adaptive multiresistant strains of genotype Beijing: in tuberculous spondylitis, which is the most severe and frequent form of osteoarticular tuberculosis, 70 of the 78 (89.7%) Mycobacterium tuberculosis isolates with MDR/XDR belong to this genotype. In pulmonary tuberculosis the XDR growth rate exceed those in extrapulmonary tuberculosis: from 26.8% (III period) to 39.5% (IV period) and, accordingly, from 8.0 to 8.6%. The situation with drug resistance in all localizations of the disease may be characterized as extremely tense, which can lead to unpredictable consequences, if promptly one not take appropriate measures.